Systematic review of rugby injuries in children and adolescents under 21 years - Freitag, A.; Kirkwood, G.; Scharer, S.; Ofori-Asenso, R.; Pollock, A. M. (British Journal of Sports Medicine, 2015)
A systematic review of rugby union and league injuries among players under the age of 21 years was carried out to calculate probabilities of match injury for a player over a season and a pooled estimate of match injury incidence where studies were sufficiently similar. The probability of a player being injured over a season ranged from 6% to 90% for rugby union and 68% to 96% for rugby league. The pooled injury incidence estimate for rugby union was 26.7/1000 player-hours for injuries irrespective of need for medical attention or time-loss and 10.3/1000 player-hours for injuries requiring at least 7 days absence from games; equivalent to a 28.4% and 12.1% risk of being injured over a season. Study heterogeneity contributed to a wide variation in injury incidence. Public injury surveillance and prevention systems have been successful in reducing injury rates in other countries. No such system exists in the UK.